2014
DOI: 10.1515/pz-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Ein „Götterbildbeschlag“ aus der Uckermark als Zeugnis mittelalterlicher Glaubensvorstellungen im nordwestslawischen Raum

Abstract: Zusammenfassung: Das Bruchstück eines figürlich verzierten Messerscheidenbeschlags (um 1000/frühes 11. Jahrhundert) von einer spätslawischen Siedlung bei Melzow in der Uckermark kann den sog. „Götterbildbeschlägen“ nach I. Gabriel zugeordnet werden. Es gehört offenkundig in reli giösen Kontext und zeigt wohl eine Szene, bei der eine Gottheit Segen und Leben an Mensch und Tier spendet. Der Fund wird vor dem Hintergrund der paganen Glaubensvorstellungen der Liutizen und zusammen mit seinen Parallelen kulturhisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
1
4
0
1
Order By: Relevance
“…Recent analysis of the distribution of Western Slavic chamber graves in the Piast state has shown that they are predominantly located close to major strongholds and supra-local centres of political, administrative, and religious power (Błaszczyk, 2016: 38). Their chronology is also significant for the present discussion, as they emerge in the tenth-eleventh centuries and continue to be built in the coastal areas of Pomerania until the eleventh-twelfth centuries (Biermann, 2008), which fits what we know from textual sources about the social and political transformations and the process of state formation in these areas. In view of their chronology, distribution, and wealth (see below), there are strong reasons to identify chamber graves with the final resting places of elites.…”
Section: The Treatment Of the Deadsupporting
confidence: 55%
See 2 more Smart Citations
“…Recent analysis of the distribution of Western Slavic chamber graves in the Piast state has shown that they are predominantly located close to major strongholds and supra-local centres of political, administrative, and religious power (Błaszczyk, 2016: 38). Their chronology is also significant for the present discussion, as they emerge in the tenth-eleventh centuries and continue to be built in the coastal areas of Pomerania until the eleventh-twelfth centuries (Biermann, 2008), which fits what we know from textual sources about the social and political transformations and the process of state formation in these areas. In view of their chronology, distribution, and wealth (see below), there are strong reasons to identify chamber graves with the final resting places of elites.…”
Section: The Treatment Of the Deadsupporting
confidence: 55%
“…We shall not discuss the meaning of this imagery in detail here, but note that several scholars (e.g. Biermann, 2014; Szczepanik, 2017) have recently argued that the scene can be interpreted as a world-model or axis mundi . This consists of a representation of the three tiers of the Slavic cosmos, with the snake being a hypostasis of the supreme god of the underworld (known as Weles or Triglav), the anthropomorphic figure on the opposite side of the bar the sky god (known as Perun or Sventovit), and the different animals along the bar the mediators between the worlds or human souls in zoomorphic form.…”
Section: Knives and Knife Sheathsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Gardeła, Kajkowski i Söderberg 2019, s. 67: "The find from Oldenburg, together with similar sheaths (albeit with somewhat simplified ornaments) known predominantly from the area of today's Poland, is considered by some scholars as a model of the Slavic cosmos (e.g. Biermann 2014;Gardeła 2017, pp. 55-61;Szczepanik 2017)".…”
Section: W Odpowiedzi Pawłowi Szczepanikowimentioning
confidence: 99%
“…11 Na podstawie dostępnej literatury (Szczepanik 2010;Biermann 2014;Kowalska 2016) znamy dzisiaj 20 podobnych znalezisk okuć pochewek noży z mniej lub bardziej rozbudowanym wątkiem ikonograficznym. Są to okucia (rozbudowane) z Oldenburga, Brześcia Kujawskiego, Schwedt nad Odrą, Ostrowa Lednickiego, Melzow oraz (prostsze) z Dziekanowic, Kałdusa (2 egz.…”
unclassified